Information System Policy of Web-based Patient Safety Incident Reporting Information System at RSJ Prof Dr. Soerojo Magelang - Purnomo, Setyo; Widodo, Aris Puji; Setyaningsih, Yuliani (UI Scholars Hub, 2020)
To provide security to their patients, healthcare providers use a system for patient safety which includes risk reporting and analysis of incidents, identification and management of risks, and the ability to learn about events that have occurred. According to the 2017 patient safety data at Prof. Dr. Soerojo Psychiatric Hospital, 7% of patient safety incidents at the hospital required a Root Cause Analysis. To aid the process, an online information system is necessary. This research was qualitative research that used the waterfall method for the information syntax. This involved planning, analysis, design, implementation, and system. From there, the data was then evaluated based on its accessibility, completeness, accuracy, and speed. The qualitative data was gathered through questionnaires, in-depth interviews, and unstructured interviews with selected informants. 26 informants were involved in this research, this included the reporters, the Patient Safety (KPRS) Team, and the hospital management board. Results of the would then produce recommendations on how to handle the problems found. Based on the data gathered, we discovered that after the application of the information system, the hospital experienced a 53.8% increase in patient safety.